The application of mental training in the rehabilitation of stroke patients - Review and calculating effect sizes - Ziemainz, Heiko; Hendrich, Simon Klaus; Schleinkofer, Michael; Pfeifer, Klaus (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2008)
In the rehabilitation of stroke patients, mental training is increasingly attracting attention as a promising psychological complement of common exercise therapy approaches [1,2]. This article aims at an analytical description of the empirical medical evidence and at the identification and assessment of the effects of mental training in the rehabilitation of stroke patients by calculating effect sizes. First of all in a systematic literature review all studies should be identified that applied mental training as an intervention for the rehabilitation of adult stroke patients. In total, 49 studies were identified and then classified based on their quality [3]. Of these, five were either randomized (4) or clinical (1) controlled studies, which formed the basis for calculating effect sizes [4]. The analysis yielded medium (ES >0.5) to high (ES >0.8) effect sizes [5]. Given these results, it seems advisable to apply mental training as a (additional) treatment in the rehabilitation of stroke patients. © Georg Thieme Verlag KG Stuttgar
Keywords: Hemiplegia; Mental practice; Mental training; Motor imagery; Rehabilitation; Stroke